“Babatehi” Kesenjangan Sosial Terhadap Pemberian Gala di Pariaman - Salsabila Filjamiati; Ariefin Alham Jaya Putra; Adjuoktoza Rovylendes; Emri (JURNAL ILMIAH NUSANTARA, 2025)
The Babatehi dance is inspired by the tradition of giving gala to married men (urang sumando) in the Pariaman community of West Sumatra. This tradition reflects a matrilineal kinship system and respect for sons-in-law, but also gives rise to different behaviors depending on the title held, such as Sidi, Sutan, and Bagindo. These differences in behavior are a clear reflection of social inequality within the family and community. The artist interprets this social phenomenon in a dramatic dance form using seven female dancers and accompanied by live experimental music. The work is structured into three sections: differences in behavior based on social status, conflicts resulting from this inequality, and the search for human equality in the eyes of God. The concept combines elements of tradition, contemporary movement exploration, and the symbolism of props to enhance its meaning. Babatehi serves not only as an artistic representation of local tradition but also as a social critique of realities that persist today.